Soluble dipeptidyl peptidase-4 induces microvascular endothelial dysfunction through proteinase-activated receptor-2 and thromboxane A2 release. Issue 5 (May 2016) - Romacho, Tania; Vallejo, Susana; Villalobos, Laura A.; Wronkowitz, Nina; Indrakusuma, Ira; Sell, Henrike; Eckel, Jüergen; Sánchez-Ferrer, Carlos F.; Peiró, Concepción
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Dipeptidyl peptidase-4 (DPP4) is a key protein in glucose homeostasis and a pharmacological target in type 2 diabetes mellitus. This study explored whether the novel adipokine soluble DPP4 (sDPP4) can cause endothelial dysfunction, an early marker of impaired vascular reactivity. Method: Reactivity was studied in mesenteric arteries from 3-month-old female mice, using a small vessel myograph. Thromboxane A2 (TXA2 ) release was explored in cultured human coronary artery endothelial cells by enzyme immunoassay. Results: Neither the contractility to noradrenaline nor the endothelium-independent relaxations induced by sodium nitroprusside were modified by sDPP4. However, sDPP4 impaired in a concentration-dependent manner the endothelium-dependent relaxation elicited by acetylcholine. The DPP4 inhibitors K579 and linagliptin prevented the defective relaxation induced by sDPP4, as did the protease-activated receptor 2 (PAR2) inhibitor GB83. Downstream of PAR2, the cyclooxygenase (COX) inhibitor indomethacin, the COX2 inhibitor celecoxib or the thromboxane receptors blocker SQ29548 prevented the deleterious effects of sDPP4. Accordingly, sDPP4 triggered the release of TXA2 by endothelial cells, whereas TXA2 release was prevented by inhibiting DPP4, PAR2 or COX. Conclusion: In summary, these findings reveal sDPP4 as a direct mediator of endothelial dysfunction, acting through PAR2 activation and the release of vasoconstrictor prostanoids. By interfering with these actions, DPP4 inhibitors might help preserving endothelial function in the context of cardiometabolic diseases.